The Role of Experiential Marketing, Perceived Value, and Sharia Service Quality as Determinants of Customer Satisfaction - Diskhamarzaweny (Ilomata International Journal of Management, 2023)
This study aims to analyze the role of Experiential Marketing, Perceived Value, and Sharia Service Quality on Customer Satisfaction of Bank Syariah Indonesia in Teluk Kuantan City. This study involves 120 samples as respondents using the Purposive Sampling method, whereas the sample criteria are customers of Bank Syariah Indonesia, Teluk Kuantan City. They have been with the Bank for at least 1 year. The data are collected from the structured questionnaire distributed to all respondents. As for the data analysis, Multiple Linear Regression method with SPSS Version 26 software is implemented. The results of this study prove that the Experiential Marketing, the Perceived Value, and the Sharia Service Quality have a positive and significant effect on Customer Satisfaction. In addition, it is emphasized that 62,8% of Customer Satisfaction is affected by Experiential Marketing, Perceived Value, and Sharia Service Quality. The perceived value is the variable with the most effects on customer satisfaction at Bank Syariah Indonesia in Teluk Kuantan City.